The Effectiveness of the Distribution of Zakat, Infaq and Sadaqah Funds by BAZNAS: A Comparative Study of South Kalimantan and West Java Provinces in 2019–2023 - Fitriyani, Yuli; Putriana, Astia; Abdillah, M. Riduan; Machfiroh, Ines Saraswati; Hadiani, Yasir (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2025)
The effective and targeted distribution of zakat and infaq/sadaqah is the biggest challenge faced by zakat management bodies. This research was conducted to determine the level of effectiveness and performance of BAZNAS in distributing zakat and infaq/sadaqah using activity ratios, by comparing BAZNAS of South Kalimantan Province and BAZNAS of West Java Province. This study is different with previous studies in terms of providing a broader picture by comparing the effectiveness and performance of the distribution of Zakat and Infaq/Sadaqa funds in two provinces with contrasting Muslim population characteristics, namely West Java Province as the province with the largest Muslim population, and South Kalimantan Province which is in 14th position. The research method uses a type of quantitative descriptive data with secondary data, namely fund change reports for the period 2019-2023. The research results show that BAZNAS of South Kalimantan Province and BAZNAS of West Java Province have distributed zakat and infaq/sadaqah funds very effectively, based on the Zakat Allocation Ratio and Infaq and Sadaqah Ratio which obtained values 90%. The performance of BAZNAS of South Kalimantan Province in distributing ZIS funds has been excellent, based on the six ratios used, achieving a value 1. Meanwhile, at BAZNAS West Java Province, out of the six ratios used, only two ratios were categorized as not good, namely the Infaq Sadaqah Turnover Ratio and the Average of Days Infaq Sadaqah Outstanding in 2020 and 2022. This is because, in those years, the collected infaq/sadaqah funds could not be distributed properly, as the funds disbursed were lower than the funds collected, causing the funds to remain idle for too long. This study indicates that the effectiveness of zakat institutions is not always influenced by the great potential of the population of the people in the region but depends on internal management and institutional distribution strategies.Pendistribusian zakat dan infaq/sadaqah yang efektif dan tepat sasaran merupakan tantangan terbesar yang dihadapi oleh lembaga pengelola zakat. Penelitian ini dilakukan untuk mengetahui tingkat efektivitas dan kinerja BAZNAS dalam menyalurkan zakat dan infaq/sadaqah menggunakan rasio aktivitas, dengan membandingkan BAZNAS Provinsi Kalimantan Selatan dan BAZNAS Provinsi Jawa Barat. Penelitian ini berbeda dengan penelitian sebelumnya dalam hal memberikan gambaran yang lebih luas dengan membandingkan efektivitas dan kinerja penyaluran dana Zakat dan Infaq/Sadaqah di dua provinsi dengan karakteristik penduduk muslim yang kontras, yaitu Provinsi Jawa Barat sebagai provinsi dengan penduduk muslim terbesar, dan Provinsi Kalimantan Selatan yang berada pada posisi ke-14. Metode penelitian menggunakan jenis data deskriptif kuantitatif dengan data sekunder yaitu laporan perubahan dana periode 2019-2023. Hasil penelitian menunjukkan bahwa BAZNAS Provinsi Kalimantan Selatan dan BAZNAS Provinsi Jawa Barat telah menyalurkan dana zakat dan infaq/sadaqah dengan sangat efektif, berdasarkan Nisbah Alokasi Zakat dan Nisbah Infaq dan Sedekah yang memperoleh nilai 90%. Kinerja BAZNAS Provinsi Kalimantan Selatan dalam menyalurkan dana ZIS sudah sangat baik, berdasarkan keenam rasio yang digunakan memperoleh nilai 1. Sementara itu, pada BAZNAS Provinsi Jawa Barat, dari keenam rasio yang digunakan, hanya dua rasio yang masuk kategori kurang baik, yaitu Rasio Perputaran Infaq Sedekah dan Rata-rata Hari Beredar Infaq Sedekah tahun 2020 dan 2022. Hal ini dikarenakan pada tahun-tahun tersebut dana infaq/sadaqah yang terkumpul belum dapat tersalurkan dengan baik, karena dana yang disalurkan lebih kecil dari dana yang terhimpun, sehingga dana tersebut terlalu lama menganggur. Penelitian ini menunjukkan bahwa efektivitas lembaga zakat tidak selalu dipengaruhi oleh besarnya potensi jumlah penduduk suatu daerah, tetapi tergantung pada manajemen internal dan strategi penyaluran lembaga.